Cross-Cultural Comparisons on Surrogacy and Egg Donation Interdisciplinary Perspectives from India, Germany and Israel (Springer International Publishing, 2018)
This book is the first to bring together an interdisciplinary collection of essays on surrogacy and egg donation from three socially, legally and culturally distinct countries - India, Israel and Germany. It presents contributions from experts in the field of social and cultural sciences, bioethics, law as well as psychology and provides critical-reflective comparative analysis of the socio-ethical factors shaping surrogacy and egg donation practices across these three countries. This book highlights the importance of a comparative perspective to 'make sense' of controversies and transitions in this highly contested area of artificial reproductive technologies. It demonstrates how local developments cannot be isolated from global events and vice versa. Therefore, this volume can be used as a standard reference for anyone seeking to understand surrogacy and egg donation from a macro-perspective in the next decade.